(untitled) (Impetus, 2024)
In soccer, players and different aspects of the game have been extensively investigated. Likewise, in recent years, there has been a trend of studying soccer referees due to their influence on the matches’ results. In Colombia, official matches have not studied soccer referees’ aspects such as distance covered, heart rate behavior, hydration status, and other elements that can help characterize this population and create intervention strategies aligned with their needs. Objective: To establish the physical load and the behavior of biomarkers associated with the physical load in soccer referees. Methods: Using a descriptive, cross-sectional study with a sample of 15 subjects (intentionally chosen) who had previously signed the informed consent form. A GPS constantly followed them, measuring their heart rate and monitoring mass, perceived exertion, and urine specific gravity before, at halftime, and after a soccer game. Results: Central and assistant referees presented differences between external and internal physical load according to their specific practice. Conclusions: There are differences between referees and assistant referees concerning the internal and external physical load; compared with other antecedents, it was possible to appreciate lower distances covered by the Quindío referees.